The Covid-19 Pandemic and its Effects on Fintech in India: A Comprehensive Review - Rehmat, Alfishan; Ahmad Ansari , Prof. Saghir (International Journal of Engineering and Technology, 2024)
This research paper aims to identify the challenges and opportunities of the COVID-19 pandemic on Indian Financial Technology. This study covers the areas of Indian Fintech, the impact of COVID-19 on fintech, and the challenges and opportunities of Indian fintech. The study used systematic literature review concept mapping to produce data from related studies conducted during the pandemic. A qualitative data analysis technique was practiced, and the data was collected from secondary sources such as annual reports of the World Health Organization (WHO), Financial Stability Board (FSB), Reserve Bank of India (RBI), and other sources. This review tries to shed light on the emerging literature and find the answers that can suggest a clear understanding of the challenges and opportunities faced by Indian Financial Technology during the COVID-19 pandemic. Findings include a positive effect of COVID-19 on Indian financial technology as more and more people shift from traditional financial services to digital financial services due to COVID-19. Prominent opportunities and challenges for the Indian fintech resulting from the impact of the COVID-19 pandemic, including increased use of fintech through online shopping platforms, payments, and loans; accelerated digitalization of financial services; slowed economic activity; arose various risks; and decreased debtors’ performance due to the impact of the pandemic. This systematic literature review helped the academic community to understand the impact of COVID-19 on the FinTech industry in India. Also, assist policymakers with the regulatory and policy changes needed to support the progress and resilience of the FinTech sector in the face of future disruptions. The literature will assist policymakers in planning post-COVID-19 economic recovery. This study helps industry practitioners to know consumer behavior shifts, technological advancements, and emerging market trends post-COVID-19.